Examining the Overlapping Jurisdictions between the WTO and AfCFTA Dispute Settlement Mechanisms: Whose Jurisdiction Is It Anyway? - Tegegn, Yehualashet Tamiru (Bahir Dar University Journal of Law, 2023)
Under the World Trade Organization (hereinafter referred to as WTO) legal framework, at least in principle, there should not be discrimination between and among member states. This principle is further reinforced by the two core non-discriminatory provisions: national treatment and mostfavored-nation treatment. This principle is not without exception, however. The different enabling clauses and specifically Article XXIV allows regional trade agreements to deviate from and provide preferential treatment. WTO system, however, lacks clarity and nowhere does it specify how to regulate the competency of the jurisdiction between the WTO and regional trade agreements dispute settlement mechanisms. This will in turn pose the greatest danger of assumption of jurisdiction by both forums and leads to forum shopping and irreconcilable decisions. Therefore, this piece of reflection tries to unpack one of the lingering questions of whether AfCFTA dispute settlement or the WTO dispute settlement body will have the competency to examine and provide valid judgement.